A novel microdeletion syndrome involving 5q14.3-q15: clinical and molecular cytogenetic characterization of three patients - Engels, Hartmut (Nature Publishing Group, 2009)
Molecular karyotyping is being increasingly applied to delineate novel disease causing microaberrations and related syndromes in patients with mental retardation of unknown aetiology. We report on three unrelated patients with overlapping de novo interstitial microdeletions involving 5q14.3-q15. All three patients presented with severe psychomotor retardation, epilepsy or febrile seizures, muscular hypotonia and variable brain and minor anomalies. Molecular karyotyping revealed three overlapping microdeletions measuring 5.7, 3.9 and 3.6 Mb, respectively. The microdeletions were identified using single nucleotide polymorphism (SNP) arrays (Affymetrix 100K and Illumina 550K) and array comparative genomic hybridization (1 Mb Sanger array-CGH). Confirmation and segregation studies were performed using fluorescence in situ hybridization (FISH) and quantitative PCR. All three aberrations were confirmed and proven to have occurred de novo. The boundaries and sizes of the deletions in the three patients were different, but an overlapping region of around 1.6 Mb in 5q14.3 was defined. It included five genes: CETN3, AC093510.2, POLR3G, LYSMD3 and the proximal part of GPR98/MASS1, a known epilepsy gene. Haploinsufficiency of GPR98/MASS1 is probably responsible for the seizure phenotype in our patients. At least one other gene contained in the commonly deleted region, LYSMD3, shows a high level of central nervous expression during embryogenesis and is also, therefore, a good candidate gene for other central nervous system (CNS) symptoms, such as psychomotor retardation, brain anomalies and muscular hypotonia of the 5q14.3 microdeletion syndrome.